Size‐Dependency of Gold Nanoparticles on TiO2 for CO Oxidation. Issue 12 (18th September 2018) - Shao, Bin; Zhang, Junying; Huang, Jiahui; Qiao, Botao; Su, Yang; Miao, Shu; Zhou, Yan; Li, Dan; Huang, Weixin; Shen, Wenjie
Abstract: Size‐controlled Au colloids in the range of 2–5 nm are synthesized in aqueous phase solution and deposited on TiO2, yielding Au/TiO2 catalysts containing relatively uniform gold particles with mean sizes of 2.2, 3.4, and 4.8 nm. Detailed structural analyses verify that the shape of Au particles evolve from a flat polyhedral to a rounded truncated‐octahedron when increasing the size from 2.2 to 4.8 nm because smaller gold particles have a higher adhesion energy on TiO2 . The atomic configurations of Au particles and the Au‐TiO2 interfacial perimeters are quantitatively analyzed as a function of Au particle size. Smaller gold particles show apparently much higher activity for low‐temperature oxidation of CO than the big ones, primarily because of the rich number of active sites at the interfaces. Specific reaction rates, normalized with the total length of the interfacial perimeters in the catalysts, however, are essentially identical. This suggests that the size effect of Au particles, in the range of 2–5 nm, originates from the bonding strength between Au nanoparticles and TiO2 surfaces. Abstract : Gold nanoparticles have prominent size effect in catalyzing low‐temperature oxidation of CO. Relatively uniform gold particles with mean sizes of 2.2, 3.4, and 4.8 nm are deposited onto TiO2, and smaller gold particles show apparently a much higher activity than the big ones, primarily because of the rich number of active sites at the Au‐TiO2 interfaces.